2011
DOI: 10.1007/s00431-011-1542-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric tick-borne infections of the central nervous system in an endemic region of Sweden: a prospective evaluation of clinical manifestations

Abstract: Pediatric tick-borne CNS infections are unexpectedly common and should be considered in children with unspecific and unexplained acute CNS-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
(46 reference statements)
0
9
0
7
Order By: Relevance
“…The large proportion of children do present with meningitis followed by meningoencephalitis. Children with meningoencephalomyelitis and radiculitis did form only a minor subgroup [15,18]. It appears from these studies that one fourth of all children will present with moderate to severe symptoms initially.…”
Section: Prognosismentioning
confidence: 94%
See 1 more Smart Citation
“…The large proportion of children do present with meningitis followed by meningoencephalitis. Children with meningoencephalomyelitis and radiculitis did form only a minor subgroup [15,18]. It appears from these studies that one fourth of all children will present with moderate to severe symptoms initially.…”
Section: Prognosismentioning
confidence: 94%
“…Cases that involve the white matter of the central nervous system (CNS) including the brainstem and myelon are on record but are exceedingly rare [16][17][18]. Two recent studies from Sweden showed that TBE in children can present also as a nonspecific inflammatory disease with a restricted encephalitic profile compared to adults making the diagnosis difficult in selected cases [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Die FSME verläuft bei Kindern und Jugendlichen häufig unspezifisch mit den Symptomen eines grippalen Infektes und somit gutartiger [20,21]. In den letzten Jahren häufen sich jedoch auch Berichte über langwierige neurologische Funktionsstörungen bei Kindern [11, 22 -34].…”
Section: Leitsymptomeunclassified
“…In children and adolescents, TBE is often nonspecific with symptoms of a flu infection and is thus more benign than in adults [20,21]. In recent years, however, there have been reports of children with protracted neurological dysfunction [11,[22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Principal Symptomsmentioning
confidence: 99%